Laminate having a function as a transparent conductive film
The laminate of an IZO film and an oxide film addresses the challenge of resistivity increase in IZO films during annealing by maintaining low resistivity and high transmittance, making it suitable for devices requiring thermal processing.
Patent Information
- Application Number
- JP2021201176
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-10
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-12-10
AI Technical Summary
IZO films experience an increase in resistivity when annealed above 220-250°C, making them unsuitable for devices requiring a heating process while maintaining high transmittance.
A laminate composed of an IZO film and an oxide film is developed, where the oxide film is laminated on top of the IZO film, preventing an increase in resistivity during annealing at 350°C while maintaining high transmittance.
The laminate achieves a surface resistance of 200Ω/sq. or less and an average visible light transmittance of 85% or more when annealed at 350°C, effectively addressing the resistivity increase issue while maintaining transparency.
Smart Images

Figure 0007655845000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate having a function as a transparent conductive film. [Background technology]
[0002] IZO (Indium-Zinc-Oxide) films, like ITO (Indium-Tin-Oxide) films, have characteristics such as low resistivity, high transmittance, and ease of fine processing, and are therefore widely used as transparent conductive films, including electrode materials for displays. Currently, most IZO films in industrial production are formed using the so-called sputtering film formation method, in which a sintered body containing IZO as a component is used as a sputtering target, as this method can be produced uniformly over a large area with good productivity.
[0003] IZO films are amorphous when formed at room temperature, and have low resistance even without crystallization, so they are mainly used in low-temperature processes (film substrates, organic EL devices, etc.). On the other hand, IZO films have a higher transmittance to near-infrared light than ITO films, so their use in sensors that use near-infrared light is being considered. However, when IZO films are annealed in air at temperatures exceeding 220-250°C, they become highly resistive, making them difficult to use as transparent conductive films in devices that require heating processes.
[0004] The applicant previously filed an application for an invention relating to a laminate in which an oxide film is laminated on an ITO film (Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent application 2021-074650 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a laminate capable of maintaining high transmittance while preventing an increase in resistivity due to annealing. [Means for solving the problem]
[0007] In order to solve the above problems, the present inventors have conducted extensive research and have found that a laminate in which an oxide film is laminated on an IZO film can achieve high transmittance while preventing an increase in resistivity due to annealing. In view of this finding, the present invention provides the following embodiments. 1) A laminate in which an IZO film and an oxide film are laminated, and when annealed in air at 350°C, the laminate has a surface resistance of 200 Ω / sq. or less, and when annealed in air at 350°C, the laminate has an average transmittance of 85% or more for visible light (wavelength: 380 to 780 nm). 2) A laminate in which an IZO film and an oxide film are laminated, in which when the surface resistance of the laminate that has not been annealed is Rs0 and the surface resistance of the laminate that has been annealed in the air at 350°C is Rs1, Rs1 / Rs0 is ≦10.0, and when the laminate has been annealed in the air at 350°C, the average visible light transmittance of the laminate is 85% or more. 3) The laminate according to 2) above, in which Rs1 / Rs0<5.0 and the average visible light transmittance of the laminate when annealed at 350° C. in air is 85% or more. 4) The laminate according to the above item 2), in which Rs1 / Rs0<2.0 and the average visible light transmittance of the laminate when annealed at 350° C. in air is 85% or more. 5) A laminate in which an IZO film and an oxide film are laminated, and the surface resistance of the laminate is R s And I When the thickness of the ZO film is T, Rs×T≦1.0×10 -3 A laminate having a resistivity of Ω·cm and an average transmittance of 85% or more for visible light (wavelength: 380 to 780 nm). 6) The laminate according to any one of 1) to 5) above, which has an average near-infrared (wavelength: 800 to 1400 nm) transmittance of 85% or more when annealed at 350° C. in air. 7) The laminate according to any one of 1) to 6) above, wherein the oxide film has a thickness of 90 nm or less. 8) The laminate according to any one of 1) to 7) above, wherein the laminate has a refractive index of 2.0 or less. 9) The laminate according to any one of 1) to 8) above, which is a laminate in which an IZO film and an oxide film are laminated, and the oxide film is made of an oxide containing Ga. 10) The laminate according to 9) above, which is a laminate having an IZO film and an oxide film laminated thereon, wherein the oxide film is made of an oxide containing at least one of Zn and Si. Effect of the Invention
[0008] The laminate according to the present embodiment has an excellent effect of preventing an increase in resistivity due to annealing while maintaining high transmittance. In addition, by laminating a specific oxide film on an existing IZO film, it has an excellent effect of easily providing a transparent conductive film with good characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Normally, when a single IZO film is annealed in air, its resistivity (surface resistance) increases, and it is no longer able to function as a transparent conductive film. In the case of a single IZO film, it is thought that oxygen penetrates into the IZO film during annealing, reducing the carrier concentration and increasing the resistivity. Although the details of the mechanism by which a specific oxide film is laminated onto the IZO film to prevent an increase in resistivity are unclear, it is thought that the oxide film acts as a protective film that suppresses the penetration of oxygen into the IZO film, thereby suppressing an increase in resistivity.
[0010] The first embodiment of the present invention is a laminate in which an IZO film and an oxide film are laminated, and is characterized in that the surface resistance of the laminate when annealed in air at 350°C is 200 Ω / sq. or less. If the surface resistance is at least 200 Ω / sq. or less, the desired conductivity can be ensured. Preferably, the surface resistance is 150 Ω / sq. or less, and more preferably, the surface resistance is 100 Ω / sq. or less.
[0011] The laminate according to the first embodiment is characterized in that the laminate has an average visible light (wavelength: 380 to 780 nm) transmittance of 85% or more when annealed in air at 350° C. The desired transparency can be ensured as long as the average visible light (wavelength: 380 to 780 nm) transmittance is at least 85% or more. The average transmittance is preferably 87% or more, and more preferably 90% or more.
[0012] Transparent conductive films are used in a variety of applications, including solar cells, and are subjected to a thermal load during the manufacturing process, resulting in the annealed state referred to in this disclosure. When subjected to a thermal load of a certain temperature or higher, the IZO film crystallizes, but the laminated oxide film maintains an amorphous state. It is believed that the ability to maintain this amorphous state contributes greatly to suppressing the increase in resistivity.
[0013] Since the degree of thermal load applied to the transparent conductive film depends on the manufacturing process, it is not important to specify the annealing temperature. In other words, the laminate according to this embodiment can suppress an increase in resistivity even when annealed at a high temperature, and it is not necessary for it to actually be annealed. At least, when annealed at a temperature of 350° C., the upper Any material that can obtain the above-mentioned predetermined surface resistance and visible light transmittance (near-infrared transmittance) is included in the laminate of this embodiment.
[0014] The second embodiment of the present invention is a laminate in which an IZO film and an oxide film are laminated, and when the surface resistance of the laminate without annealing is Rs0 and the surface resistance of the laminate when annealed in air at 350°C is Rs1, Rs1 / Rs0≦10.0. In the case of an IZO single film, when annealing is performed in air at 350°C, the surface resistance increases by 10 times or more compared to the case without annealing (As-Depo). On the other hand, when a predetermined oxide film is laminated on the IZO film, it is possible to significantly suppress the increase in surface resistance even when annealing in air at 350°C. Preferably, Rs1 / Rs0<5.0, more preferably Rs1 <Rs0<2.0である。
[0015] The laminate according to the second embodiment has an average visible light (wavelength: 380 to 780 nm) transmittance of 85% or more when annealed in air at 350° C. As long as the average visible light (wavelength: 380 to 780 nm) transmittance is at least 85% or more, the desired transparency can be ensured. The average transmittance is preferably 87% or more, and more preferably 90% or more.
[0016] The third embodiment of the present invention is a laminate in which an IZO film and an oxide film are laminated, and the surface resistance of the laminate is R s When the thickness of the IZO film is T, Rs×T≦1.0×10 -3 The volume resistivity of the laminate depends on the film thickness, and when the film thickness of the IZO film is T, satisfying the above relational expression can be said to have good characteristics as a conductive film. In this case, the annealing temperature (the temperature at which the heating process was performed) is not particularly important, and laminates that satisfy the above relational expression are included in the scope of this embodiment.
[0017] The laminate according to the third embodiment has an average visible light (wavelength: 380 to 780 nm) transmittance of 85% or more when annealed in air at 350° C. As long as the average visible light (wavelength: 380 to 780 nm) transmittance is at least 85% or more, the desired transparency can be ensured. The average transmittance is preferably 87% or more, and more preferably 90% or more.
[0018] In any of the first, second and third embodiments, the laminate preferably has an average near-infrared (wavelength: 800 to 1400 nm) transmittance of 85% or more when annealed at 350° C. More preferably, the average transmittance is 90% or more. Since the IZO film is being considered for use in sensors using near-infrared light, it is more preferable that the transmittance in the near-infrared region is high.
[0019] In any of the first, second, and third embodiments, the thickness of the oxide film is not particularly limited, but the thickness is preferably 90 nm or less. If the film thickness is too thick, the resistivity of the laminate may increase. More preferably, the film thickness is 70 nm or less, and even more preferably, the film thickness is 50 nm or less. On the other hand, if the film thickness is too thin, the increase in the resistivity of the IZO film may not be sufficiently suppressed, so the film thickness is preferably 10 nm or more. However, since the effect of suppressing the increase in resistivity and the effect of improving the transmittance are affected by the type and composition of the oxide film, it is preferable to adjust the film thickness depending on the type of the oxide film, etc.
[0020] In any of the first, second, and third embodiments, the refractive index of the laminate is preferably 2.0 or less. By laminating an oxide film having a low refractive index on the IZO film, the reflectance can be reduced and the transmittance can be improved.
[0021] As oxide films that can maintain an amorphous state, for example, oxides containing Ga, In addition, oxide films made of oxides containing at least one of Zn and Si are also included. There are no limitations on the content of these elements, and oxide films containing 100 mol% or less of Ga calculated as Ga2O3, or 80 mol% or less of Zn calculated as ZnO, and oxide films containing less than 100 mol% of Si calculated as SiO2 are preferred.
[0022] In the present disclosure, the IZO film is a film mainly composed of ZnO and In2O3, and although there is no particular limit to the composition ratio, it is preferable that ZnO is 7 to 30 wt%, with the remainder being In2O3. If the composition ratio of ZnO is low, the crystallization temperature tends to be easily lowered. On the other hand, if the composition ratio of ZnO is high, the resistance of the IZO film itself increases, and it may become difficult to function as a transparent conductive film.
[0023] The method for producing the laminate of the present invention will be specifically described below. The following is an example, and is not intended to be limited to this production method. It should be understood that there are other methods for producing the laminate itself. The production conditions can be changed within a range that does not significantly change the characteristics of the transparent conductive film (laminate). In order to avoid unnecessarily obscuring the disclosed production method, detailed descriptions of well-known production steps and processing operations will be omitted.
[0024] An IZO sputtering target made of an oxide containing In and Zn, and a Zn-Ga-Si-O sputtering target made of an oxide containing Zn, Ga, and Si are prepared. First, the IZO sputtering target is placed in a vacuum chamber of a sputtering device, and a film is formed on a substrate facing the sputtering target. Then, similarly, an oxide film is formed on the IZO film formed on the substrate using the Zn-Ga-Si-O sputtering target. The thickness of the oxide film can be appropriately changed by adjusting the sputtering power and sputtering time.
[0025] The sputtering conditions can be, for example, as follows. The conditions can be appropriately changed depending on the desired film thickness and the composition of the sputtering target. (Sputtering conditions) Sputtering equipment: ANELVA C-7500L Sputtering power: DC 500~1000W (For targets that cannot be DC sputtered, use RF 500~1000W) Gas pressure: 0.5Pa Substrate heating: room temperature Oxygen concentration: 0%, 2%
[0026] Thereafter, the laminate with the oxide film (Zn-Ga-Si-O) formed on the IZO film is taken out of the sputtering device, and annealed at 200 to 600°C to crystallize the IZO film. The annealing temperature can be appropriately determined in consideration of the desired resistivity and transmittance, the heat resistance temperature of the substrate, and the like. The annealing atmosphere is not limited to air, and may be an atmosphere with an adjusted oxygen concentration, or a vacuum or nitrogen atmosphere. As a result, a laminate with low resistivity and high transmittance can be obtained. Although sputtering is a method suitable for forming an oxide film, other chemical or physical vapor deposition methods may also be used.
[0027] In the above, an example was given of using a Zn-Ga-Si-O sputtering target for forming an oxide film, but other targets such as a ZnO sputtering target, a Ga2O3 sputtering target, a SiO2 sputtering target, or a Zn-Ga-O sputtering target can also be selected.
[0028] In the examples and comparative examples, the properties of the laminates were evaluated by the following methods. (Surface resistance of film) surface resistance Method: Constant current application method Equipment: NPS resistivity measuring instrument Σ-5+ Method: DC 4-probe method High resistivity case Method: constant voltage application method Equipment: Mitsubishi Chemical Analytech High Resistivity Meter Hirestar-UX Method: MCC-A method (JIS K 6911) Ring electrode probe: URS Measurement voltage: 1 to 1000V
[0029] (Membrane transmittance) Visible light / near infrared light average transmittance Equipment: SHIMADZU spectrophotometer UV-2600 Reference: Uncoated glass substrate (EagleXG) Measurement wavelength: 380~1400nm Step: 5nm
[0030] (About film thickness) Equipment: BRUKER stylus-type thin film step gauge Dektak XT
[0031] (Refractive index of film) Equipment: SHIMADZU spectrophotometer UV-2450, UV-2600 Method: Calculated from transmittance and front and back reflectance Wavelength: 550nm
[0032] (film carrier concentration / mobility) Principle: Hall measurement Equipment: Lake Shore 8400 model EXAMPLES
[0033] The present invention will be described below based on examples and comparative examples. The examples are merely examples, and the present invention is not limited by these examples. In other words, the present invention is limited only by the claims, and includes various modifications other than the examples included in the present invention.
[0034] Comparative Example 1 An IZO (ZnO: 10.7 wt%, In2O3: balance) sputtering target was attached to a sputtering device, and sputtering was performed under the above conditions to form an IZO film (single film) with a thickness of 100 nm on a substrate. In Comparative Example 1, the oxygen concentration during film formation was 2 vol% (Ar: 98 vol%). Annealing was then performed for 30 minutes in air at different temperatures. Then, the surface resistance and average visible and near-infrared transmittance of each of the obtained IZO films were measured. The results are shown in Table 1. In the table, "as-depo" refers to the film as formed (before annealing).
[0035] As can be seen from Table 1, when the annealing temperature of the IZO film was increased, the resistivity increased sharply from an annealing temperature of 300°C or higher. The resistivity then showed a high value of Rs1 / Rs0 = 14.78. The average visible light transmittance and the average near-infrared light transmittance also decreased to less than 85%. As shown in Table 1, in Comparative Example 1, the carrier concentration decreased as the annealing temperature was increased. This is believed to be due to oxygen diffusing into the IZO film during annealing.
[0036] [Table 1]
[0037] (Examples 1 and 2) The Zn-Ga-Si-O sputtering target was attached to a sputtering device, and sputtering was performed under the above conditions. An IZO film with a thickness of 100 nm was formed on the substrate, and an oxide film (Zn-Ga-Si-O) was formed on the IZO film. In Example 1, the composition of the oxide film was ZnO: 40 mol%, Ga2O3: 20 mol%, SiO2: 40 mol%, and in Example 2, the composition of the oxide film was ZnO: 83 mol%, Ga2O3: 8 mol%, SiO2: 9 mol%. In Examples 1 and 2, an oxide film with a thickness of 20 nm was formed on the IZO film formed at an oxygen concentration of 2%.
[0038] After that, annealing was performed for 30 minutes at different temperatures in the atmosphere. Then, the surface resistance and the average visible light and near infrared light transmittance were measured for each of the obtained laminates. The results are shown in Table 1. As shown in Table 1, unlike the IZO film single film, the laminate did not show a sudden increase in resistivity up to a certain temperature even when the annealing temperature was increased. In particular, Rs1 / Rs0 was significantly below 10.0, and a sudden increase in resistivity was suppressed even at an annealing temperature of 350°C. In addition, even when the annealing temperature was increased, the average visible light transmittance and the average near infrared transmittance remained at 85% or more up to a certain temperature. In this way, by forming a laminate in which an IZO film and an oxide film are laminated, it is possible to realize low resistivity and high transmittance during high-temperature annealing that could not be obtained with existing IZO films. [Industrial Applicability]
[0039] The laminate of the present invention can maintain high transmittance while preventing an increase in resistivity due to annealing, and has good functions as a transparent conductive film. In addition, the present invention can easily provide a transparent conductive film with good properties by laminating an oxide film on an IZO film. The laminate of the present invention is particularly useful as a transparent conductive film in devices (flat panel displays, micro LEDs, etc.) that use glass substrates or Si substrates that can be annealed at high temperatures.
Claims
1. A laminate in which an IZO film and an oxide film are laminated, the laminate has a surface resistance of 200 Ω / sq. or less when annealed in air at 350° C., and has an average transmittance of 85% or more for visible light (wavelength: 380 to 780 nm) when annealed in air at 350° C., and the oxide film is made of an oxide containing Ga.
2. A laminate in which an IZO film and an oxide film are laminated, wherein when the surface resistance of the laminate that has not been annealed is Rs0 and the surface resistance of the laminate that has been annealed in the air at 350° C. is Rs1, Rs1 / Rs0≦10.0, the laminate that has been annealed in the air at 350° C. has an average visible light transmittance of 85% or more, and the oxide film is made of an oxide containing Ga.
3. The laminate according to claim 2, wherein Rs1 / Rs0 is less than 5.0, and the average visible light transmittance when annealed at 350° C. in air is 85% or more.
4. 3. The laminate according to claim 2, wherein Rs1 / Rs0 is less than 2.0, and the average visible light transmittance when annealed at 350° C. in air is 85% or more.
5. A laminate in which an IZO film and an oxide film are laminated, where the surface resistance of the laminate is Rs and the thickness of the IZO film is T, Rs×T≦1.0×10 -3 A laminate having a resistivity of Ω·cm and an average transmittance of visible light (wavelength: 380 to 780 nm) of 85% or more, wherein the oxide film is made of an oxide containing Ga.
6. 6. The laminate according to claim 1, wherein the laminate has an average near-infrared (wavelength: 800 to 1400 nm) transmittance of 85% or more when annealed at 350° C. in air.
7. 7. The laminate according to claim 1, wherein the oxide film has a thickness of 90 nm or less.
8. The laminate according to any one of claims 1 to 7, wherein the refractive index of the laminate is 2.0 or less.
9. A laminate in which an IZO film and an oxide film are laminated, the oxide film being made of either Zn or Si. The laminate according to any one of claims 1 to 8, which comprises an oxide comprising the above.
Citation Information
Patent Citations
Conductive film, preparation method and applications thereof
CN104210167A
Transparent electrically conductive laminate and manufacture thereof
JP2001001441A
Oil-water separation tank
JP2021074650A